Seasonal and spatial variations in eutrophication and water quality of Lake Aha, Guiyang city, China - Yin Su; Bingze Ling; Jintong Ren (PLoS ONE, 2025)
This study aimed to analyze the spatial and temporal variations in water quality status and eutrophication level of Lake Aha, influenced by human activities and seasonal changes. Ten indicators were sampled and analyzed at seven sampling points in Lake Aha in different seasons and vertical layers. The eutrophication level and water quality status were evaluated using the Trophic Level Index (TLI) and Water Quality Index (WQI). Results showed that the average TLI and WQI values during the wet season (July) were 31.06 and 92.14, respectively, compared to 28.64 and 109.14 during the dry season (April). Eutrophication was more severe in the wet season than in the dry season, whereas water quality was poorer in the dry season than in the wet season. The main factors driving these patters were temperature and precipitation, respectively. Spatially, the northern part of Lake Aha exhibited higher eutrophication levels than the southern part, while water quality was better in the south than in the north, largely due to the impact of human activities. Significant differences in eutrophication levels and water quality were observed among the seven sampling points, though variations across vertical layers were minimal. Strong positive correlations between key indicators—such as CODMn, TP, and Chl-a—highlighted interdependencies affecting overall water quality, with these factors identified as critical drivers of TLI and WQI. These findings indicate the important impacts of seasonal changes and human activities on the water quality of Lake Aha and suggest the need for targeted water pollution management strategies.